Adaptation of Cyber Incivility Scale Indonesia Version - Febriana, Silvia Kristanti Tri; Fajrianthi, Fajrianthi (Faculty of Psychology, Universitas Diponegoro, 2022)
This research, divided into two studies, aimed to modify, and adapt the cyber incivility scale compiled by Lim and Teo (2009) in the Indonesian language and culture. Study 1, namely the process of translating the items and testing their suitability, involving six translators, three expert reviewers, and 10 participants for cognitive debriefing purposes. Meanwhile, Study 2 involved 232 workers in Indonesia who occupied structural leadership positions. The subjects consisted of 126 women (54.5%) and 106 men (45.5%) with a mean age of 36.9 years (SD = 8.64; min = 20 years; max = 64 years). At this stage, a trial of the cyber incivility scale was carried out. The scale was adapted with confirmatory factor analysis using AMOS version 22. The entire adaptation process referred to the procedures of the 2016 International Test Commission (ITC) Guidelines for Test Adaptation. The CFA results of the goodness of fit test showed fit values (CFI = .972; TLI = .966; RMSEA = .063, GFI = .909, p = .000). Therefore, it could be concluded that the cyber incivility measurement model in this study was following the cyber incivility theory of Lim and Teo (2009) with two factors. Overall, this research showed that the Indonesian version of the cyber incivility scale is valid and reliable, thus applicable to measure the cyber incivility in the context of the perpetrator in Indonesia.